2020
DOI: 10.3389/fchem.2020.589959
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Lipid Nanoparticles for mRNA-Based Cancer Immunotherapy

Abstract: Over the past decade, messenger RNA (mRNA) has emerged as potent and flexible platform for the development of novel effective cancer immunotherapies. Advances in non-viral gene delivery technologies, especially the tremendous progress in lipid nanoparticles' manufacturing, have made possible the implementation of mRNA-based antitumor treatments. Several mRNA-based immunotherapies have demonstrated antitumor effect in preclinical and clinical studies, and marked successes have been achieved most notably by its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
141
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(153 citation statements)
references
References 97 publications
0
141
0
Order By: Relevance
“…Thanks to the advances in nanoscience, a wide range of nano-carriers have been constructed in recent years to facilitate cytoplasmic delivery of mRNA ( 14 ). The nano-platforms that have been exploited for in vivo delivery of mRNA include lipid nanoparticles (LNPs; including cationic liposomes/lipoplexes with lipid bilayers, and more often with a lipid monolayer and lipophilic cores), polymer-based nanoparticles, lipid-polymer hybrids ( 15 17 ). Among these non-viral vectors, LNPs are particularly appealing and have been widely used as mRNA carriers ( 8 ), because of their biocompatible properties, ability to protect the mRNA against degradation, and flexibility to be tailored to target specific cell types (APCs, such as DCs) by surface modification with a ligand ( 16 , 17 ).…”
Section: Nanoparticles Mediated Cytoplasmicdelivery Of Mrnamentioning
confidence: 99%
“…Thanks to the advances in nanoscience, a wide range of nano-carriers have been constructed in recent years to facilitate cytoplasmic delivery of mRNA ( 14 ). The nano-platforms that have been exploited for in vivo delivery of mRNA include lipid nanoparticles (LNPs; including cationic liposomes/lipoplexes with lipid bilayers, and more often with a lipid monolayer and lipophilic cores), polymer-based nanoparticles, lipid-polymer hybrids ( 15 17 ). Among these non-viral vectors, LNPs are particularly appealing and have been widely used as mRNA carriers ( 8 ), because of their biocompatible properties, ability to protect the mRNA against degradation, and flexibility to be tailored to target specific cell types (APCs, such as DCs) by surface modification with a ligand ( 16 , 17 ).…”
Section: Nanoparticles Mediated Cytoplasmicdelivery Of Mrnamentioning
confidence: 99%
“…The structure of LNPs consists of a solid core made up of lipid, which is composed of triglycerides or any other glyceride mixture. A typical LNP has four parts: (i) an ionizable lipid portion that allows self-assembly, enhances the rate of mRNA encapsulation, and aids endosomal escape, (ii) a stabilizing agent for stability and membrane fusion (cholesterol or a sphingolipid), (iii) a phospholipid that stabilizes the bilayer, encapsulating the lipid structure [41] , and (iv) polyethylene glycol (PEG), a lipid-based stabilizing agent that reduces nonspecific binding to proteins, increases half-life, and boosts circulation time by aiding escape from first pass metabolism or reticulo-endothelial system (RES). Their rigid morphology and kinetic stability are key advantages, making LNPs, a carrier of choice over liposomes.…”
Section: The Focus On Delivery: Key Advantages Of Lipid Nanoparticlesmentioning
confidence: 99%
“…Lipoplexes are usually obtained by adding NAs to the cationic lipids in order to enable the natural assembly of the two components. So far, a number of studies have shown the ability of different cationic lipids to bind and condense NAs of various size, including DNA molecules in the form of pDNA and oligonucleotides (Caracciolo and Amenitsch, 2012;Koynova and Tenchov, 2010;Meidan et al, 2000;Tros de Ilarduya et al, 2010;Wang et al, 2015;Weisman et al, 2004), and RNA molecules, such as siRNA and mRNA (Guevara et al, 2020;Midoux and Pichon, 2014;Semple et al, 2010;Zhang et al, 2007). Therefore, when mixing NAs with cationic lipids, the size and the 3D arrangement of the former may affect the physico-chemical features and the supramolecular structure of the resulting complexes (Ewert et al, 2010;Rao, 2010;Scholz and Wagner, 2012).…”
Section: Cationic Lipids: From Structure To Aggregation Phasementioning
confidence: 99%